Factors Influencing Smes Performance In Saudi Arabia: Moderating Effect Of Access To Finance - Alharbi, Raed Khamis (2020)
In response to the challenges facing SMEs, including a lack of access to finance, a lack of management competency, and manager characteristics, this study aims to fill the literature gaps by proposing and validating the SMEs’ performance model based on the Resource-Based View theory (RBV). Drawing upon this theory, this study examines the moderating role of access to finance on the link between age, education, experience, training, Islamic religiosity, financial knowledge, and management competency on SMEs’ performance in Saudi Arabia. The current study adopted a quantitative method and rely on the cluster sampling method of data collection to divide the three regions into three clusters.